Adult resilience after child abuse. (April 2018) - Masten, Ann
Growing evidence links adverse childhood experiences to health problems decades later. A study of adults followed in midlife finds that perceived social support predicts lower subsequent mortality, particularly for adults reporting child abuse, suggesting that supportive relationships buffer long-term health in the context of early maltreatment.